2018
DOI: 10.15761/hec.1000136
|View full text |Cite
|
Sign up to set email alerts
|

Care process for stroke patients in kenya: mixed study

Abstract: Background: Longer-term impairments and activity limitations secondary to stroke can cause inability to return to work, and decreased social participation. Upon stroke episode, patients follow a series of care pathways implemented by healthcare professionals. However, this pathway differs in developing and developed countries. The purpose of this study is to determine the physiotherapy stroke rehabilitation pathway in Kenya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Twelve hospital-based studies conducted between 2003 and 2017 met the inclusion criteria ( 14 – 25 ). Six studies were retrospective ( 14 , 19 21 , 23 , 25 ) while six were prospective ( 15 18 , 22 , 24 ). One study was conducted in a rural hospital ( 18 ), and one in a private hospital ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve hospital-based studies conducted between 2003 and 2017 met the inclusion criteria ( 14 – 25 ). Six studies were retrospective ( 14 , 19 21 , 23 , 25 ) while six were prospective ( 15 18 , 22 , 24 ). One study was conducted in a rural hospital ( 18 ), and one in a private hospital ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study was conducted in a rural hospital ( 18 ), and one in a private hospital ( 19 ). Five studies were single-center ( 14 , 18 , 19 , 21 , 24 ) while seven were multicenter ( 15 17 , 20 , 22 , 23 , 25 ). One study included only cortical ischemic stroke patients ( 21 ) while one other study included only patients with chronic (over two months) strokes aged 15–49 years ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous authors [ 39 , 40 ] have shown that life-threatening problems in stroke vary in severity among patients and practice settings and that such problems may influence physicians’ decisions regarding the initiation of rehabilitation. Kingau [ 30 ] also showed that some patients admitted to hospitals in Kenya received physiotherapy one week later after their conditions had stabilised. These studies altogether suggest that the patient’s current health state is a good predictor of rehabilitation onset during the admission to hospital.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our understanding, the extent to which stroke patients in Tanzania are afflicted with stroke and subsequent disability is not known. While we know from Kingau [ 30 ] that the frequency of rehabilitation is a key determinant for recovery, the extent to which patients at the Kilimanjaro Christian Medical Centre (KCMC) get access to rehabilitation therapies during and after the admission to hospital is not known. However, stroke has been described as an important cause of admission to the KCMC.…”
Section: Introductionmentioning
confidence: 99%